Evaluating laptop replacement cycles: A multi-factor analysis for It-intensive organizations - Maltamo, Pete (2025)
Growing environmental concerns, increasing demands for cost efficiency, and evolving user expectations are prompting organizations to reassess their approach to IT asset lifecycle management. In particular, the replacement cycle of laptops. That are critical tools in knowledge-intensive work and have become a focal point for sustainability and financial optimization. This thesis investigates how laptop replacement cycles can be evaluated and extended through a multi-factor analysis, aiming to support evidence-based decision-making in IT management. Using a mixed-methods case study design, the research combines quantitative survey data, qualitative interviews, and secondary data from internal systems. The analysis explores current replacement practices in a large IT-intensive organization and compares the impacts of extending the typical three-year replacement cycle to four or five years. The study evaluates this from four key perspectives: environmental impact, IT management, financial aspects, and end-user experience. The findings suggest that with proper maintenance, support strategies, and user-device matching, longer replacement cycles can be both feasible and beneficial. Extending device use reduces costs and emissions without significantly compromising productivity, provided aging-related issues are proactively managed. The thesis contributes to both academic and practical discussions by offering a framework for evaluating replacement cycles and highlighting the conditions under which lifecycle extension supports sustainable and efficient IT operations.